A review of crude oil extraction methods from petroleum sludge - Thong, Ofellia; Amirah, Ibrahim; Hussien, Abdul Rahim; Weng, Jun Yong; Norasyikin, Ismail (Penerbit Universiti Malaysia Pahang, 2021)
The development of petrochemical refinery industries has resulted in increased production of petroleum sludge and its disposal, which poses a risk of introducing hazardous elements into the environment. Eliminating petroleum sludge from storage, processing, transportation, and pipeline systems were always a major problem for the oil and gas industry. Today there are an estimated 60 million tons of petroleum sludge produced annually. Statistics also show that one ton of oily sludge is produced for every 500 tons of crude oil processed. Therefore, the petroleum industry requires protected and environmentally friendly techniques to find alternative treatment methods for petroleum sludge. Among the possible methods, oil recovery using solvent extraction method has been widely used for petroleum sludge treatment under different experimental factors. The reason is because solvent extraction is one of the cheapest and most efficient recycling processes. In addition, it used lubricating oil that does not require water, and the solvent is reusable. However, solvent extraction alone is insufficient for extracting crude oil from a large volume of petroleum sludge due to low efficiency and high variability. Therefore, combining different methods of solvent extraction and freeze-thaw hybrid technique may improve the oil extraction efficiency. Thus, this paper reviews thorough analysis of petroleum sludge’s physical and chemical properties and its oil recovery using solvent extraction and freeze-thaw method to promote the waste-to-wealth initiative.